Análise das características perceptiveis da inovação como fatores influenciadores no processo de adoção: um estudo exploratório junto a fabricantes e usuários de cosméticos na região metropolitana de Fortaleza-CE - Vasconcelos, Maria Sueli Lopes (2011)
The technological innovation is a determining factor for the company success, especially in sectors dependent on innovation as cosmetics. Studies show that a simple innovation existence doesn t guarantee that the innovation will be adopted, there are many factors that contribute to that innovation is adopted. The importance influence of innovation on their adoption rate is related to perceived attributes of innovation. The overall goal of this research is to identify the perceived characteristics of innovation and its influence in the adoption process of innovation in the cosmetic industries. Initially was conducted a bibliography review for the construction of the theoretical foundation of the study. Was analyzed a model based on the decision of innovation paradigm proposed for Rogers (2003), showing the second stage of the model, that discusses the innovation attributes, and form that model were identified which characteristics influence the adoption of the innovative product form the perspective of a cosmetic manufacturer and their users. The Rogers s model (2003), was adequate to understand the influence of the characteristics of innovation on the cosmetics sector. The methodology used in this study consisted of a quantitative survey characterized as descriptive and exploratory, closed questionnaires were applied with three innovative companies and twenty users per company. The data were analyzed using statistical methods, average, standard deviation and variation coefficient which were analyzed through the software sphinx. The results obtained by the survey indicated that the perceived innovation characteristic that most influenced the process of adopting a technological innovation of enterprises surveyed in the cosmetic industry was the observability, followed by the relative advantages and compatibility. Regarding the perception of users, three characteristics influenced the unanimous adoption of the product, compatibility, observability and complexity. It was found by comparative analysis between the companies that the model proposed by Rogers (2003) was not supported empirically, but analyzing companies individually, says there is empirical evidence regarding this proposal.